Avaliação de inseticidas para o controle de Aryrotaenia sphaleropa (Meyrick,1909) (Lepidoptera : Tortricidae) na cultura da videira e Efeitos secundários sobre Trichogramma pretiosum (Riley,1879) (Hymenoptera : Trichogrammatidae) - Morandi Filho, Wilson José (2008)
The Argyrotaenia sphaleropa (Meyrick, 1909) (Lepidoptera:Tortricidae) is often found damaging vineyards and other temperate fruit orchards, in the Serra Gaucha region. This work was conducted to study seasonal occurrence of A. sphaleropa adults in vineyards using sexual synthetic pheromone, the effect of commercial formulations of insecticides with emphasis on that allowed in the organic production (neem, natural piretro, pirolenhoso extract and Bacillus thuringiensis) to control A. sphaleropa and their effects on the egg parasitoid Trichogramma pretiosum adults. Based on weekly evaluation A. sphaleropa adults catched in Delta trap baited with synthetic sexual pheromone (Z11,13-14Ac + Z11,13-14Al + Z11-14Al in a ratio of 4:4:1, 1000μg/septum) during 2003/2004 season, it was observed four populational peaks in a Cabernet Sauvignon vineyards. The first population peak occurred in the beginning of October, the second in the beginning of February, the third occurred in middle of March and the forth in June. In the experiments conducted in the laboratory using grapevine leaves with artificial infestations of 3st to 4th instars) and in commercial vineyard, Bacillus thuringiensis var. kurstaki (Dipel DF 50, 75 and 100 g/100L), fenitrothion (Sumithion 500 CE, 150 mL/100L) and triclhorfon (Dipterex 500, 300 mL/100L) were efficient to control A. sphaleropa larvae reducing insect population upper to 90%. In laboratory, the insecticides Natuneem® (1500 ppm of azadirachtin/L) and the pirolenhoso extract (Biopirol 7 M®) (250 and 500 mL/100L) were not efficient in the control of A. sphaleropa when applied over grapevine leaves. Natural piretro (250 and 500 mL/100L) resulted in a mortality of 77,65 and 85,88% of insects, respectively 120 hours after application. Natuneem® (0,25 e 0,50%) incorporated to A. sphaleropa artificial diet increased larval phase, reduced larval and pupae viability producing males with a reduces lifespan. Biopirol 7M® in the concentration of 0,50% increased larval duration, reduced male longevity and the oviposition period without affecting fecundity. Baseding on the fertility life table, it was verified that Natuneem® and Biopirol®, both in 0,25 and 0,50% added to artificial diets increase modified the duration in days of a generation, the liquid tax of reproduction, the infinitesimal reason of population increase and the finite reason of increase of A. sphaleropa, when compared with diet without insecticides. Secondary effects of insecticides allowed in organic production (Natuneem®, natural piretro, Biopirol 7M® and Dipel DF®) and the phosphorous compounds used in grapevine (triclorfon and fenitrotion) were evaluated on adults of the egg parasitoid Trichogramma pretiosum following IOBC methodology. The experiments were conducted exposing adults (more sensible period) of T. pretiosum to dry pesticide residues sprayed on glass plates. It was observed that Natuneem® (500 mL/100L), Biopirol 7 M® (500 mL/100L) and Dipel DF® (100g/100L) had been innocuous (<30% parasitism reduction) while natural piretro (250 mL/100L) was classified as moderad harmful (80-99% of parasitism reduction). Natural piretro in the higher dose (500 mL/100L) showed a parasitism deduction in more than 99%equivalent to fenthiom (Lebaycid 500, 100.